Assessing value in health care: using an interpretive classification system to understand existing practices based on a systematic review - Brayan V. Seixas; François Dionne; Tania Conte; Craig Mitton (BMC, 2019)
Abstract Background Implementing adequate strategies to assess the value of health services plays a central role in the effort to deal with the financial pressures faced by health care systems worldwide. This study aimed to understand which approaches to value assessment have been used in developed countries. Methods We conducted a rapid review and a gray literature search to identify value assessment frameworks. A two-stage screening process was utilized to identify existing approaches and cluster similar frameworks. In addition, we developed an interpretive classification system to make sense of existing approaches. Results One thousand one hundred seventy-six references were identified and 38 papers were selected for full-review. Among these 38 articles, 22 distinct approaches to assess value of health care interventions were identified and classified according to four points: 1) use of single or multiple considerations to base value estimates; 2) use of disease-specific or generic criteria; 3) reliance on process-based or outcomes-based consideration; and 4) type of input and evidence considered. Conclusions The contextual nature of value assessment in health care becomes evident with the diversity of existing approaches. Despite the predominance of cases relying on the Incremental cost-effectiveness ratio as the measure of value, this approach has not been sufficient to meet the needs of decision-makers. The use of multiple criteria has become more and more important, as well as the consideration of patient-reported measures. Considerations of costs are not always explicit and consistent.